Hospice Patient Care Goals and Medical Students' Perceptions: Evidence of a Generation Gap?. (February 2021) - Levy, Kathryn; Grant, Pei C.; Kerr, Christopher W.; Byrwa, David J.; Depner, Rachel M.
Background: The ability to perceive care goals of the dying may be an indicator of future quality patient-centered care. Research conducted on end-of-life goals indicates discrepancies between patients and physicians. Objective: The aim of this study is to compare end-of-life care goals of hospice patients and medical student perceptions of patient care goals. Design: Hospice patients and medical students were surveyed on their care goals and perceptions, respectively, using an 11-item survey of goals previously identified in palliative care literature. Medical student empathy was measured using the Interpersonal Reactivity Index. Settings/Participants: Eighty hospice patients and 176 medical students (97 first-year and 79 third-year) in a New York State medical school. Results: Medical students ranked 7 of the 11 care goals differently than hospice patients: not being a burden to family ( p < .001), time with family and friends ( p = .002), being at peace with God ( p < .001), dying at home ( p = .004), feeling that life was meaningful ( p < .001), living as long as possible ( p < .001), and resolving conflicts ( p < .001). Third-year students were less successful than first-year students in perceiving patient care goals of hospice patients. No significant differences in medical student empathy were found based on student year. Conclusions: Medical students, while empathetic, were generally unsuccessful in perceiving end-of-life care goals of hospice patients in the psychosocial and spiritual domains. Differences impeding the ability of medical students to understand these care goals may be generationally based. Increased age awareness and sensitivity may improve future end-of-life care discussions. Overall, there is a need to recognize the greater dimensionality of the dying in order to provide the most complete patient-centered care.